2003
DOI: 10.1023/b:brea.0000003956.11376.5b
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging-guided Focused Ultrasound Surgery of Breast Cancer: Correlation of Dynamic Contrast-enhanced MRI with Histopathologic Findings

Abstract: These results suggest that parameters from DCE-MRI data could provide a reliable non-invasive method for assessing residual tumor following MRIgFUS treatment of breast tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
107
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(110 citation statements)
references
References 24 publications
2
107
1
Order By: Relevance
“…These methods include touch frozen section analysis (25), touch preparation cytology (26), specimen radiography (27,28), rf spectroscopy (29,30), Raman spectroscopy (31), radioguided occult lesion localization (32), near-IR fluorescence (33,34), and high-frequency ultrasound (35)(36)(37). The intraoperative application of MRI, which has been successfully applied in brain surgery (38)(39)(40)(41)(42), is limited in its application in BCS.…”
mentioning
confidence: 99%
“…These methods include touch frozen section analysis (25), touch preparation cytology (26), specimen radiography (27,28), rf spectroscopy (29,30), Raman spectroscopy (31), radioguided occult lesion localization (32), near-IR fluorescence (33,34), and high-frequency ultrasound (35)(36)(37). The intraoperative application of MRI, which has been successfully applied in brain surgery (38)(39)(40)(41)(42), is limited in its application in BCS.…”
mentioning
confidence: 99%
“…IN RECENT YEARS, the treatment of breast cancer has become less invasive: from radical mastectomy to breast-conserving surgery, to minimally-invasive thermal therapies such as radiofrequency ablation, laser ablation, and focused ultrasound (1)(2)(3). Accurate thermometry is a prerequisite for the safe and reliable application of minimally-invasive thermal therapy in a clinical setting.…”
mentioning
confidence: 99%
“…The 63 articles included 16 feasibility studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28], 12 phase I studies [29][30][31][32][33][34][35][36][37][38][39][40], nine phase II studies [41][42][43][44][45][46][47][48][49], three comparative studies [50][51][52], one retrospective study [53], and four randomised controlled trials [54][55][56]. In 18 studies the type of study was not reported [8,[57][58][59][60][61][62][63][64][65]<...>…”
Section: Selected Studiesmentioning
confidence: 99%